2020
DOI: 10.3389/fpls.2020.00404
|View full text |Cite
|
Sign up to set email alerts
|

Warming Effects on Periphyton Community and Abundance in Different Seasons Are Influenced by Nutrient State and Plant Type: A Shallow Lake Mesocosm Study

Abstract: Frontiers in Plant Science | www.frontiersin.org April 2020 | Volume 11 | Article 404 Hao et al.Warming Effects on Periphyton in spring, summer, and autumn. Our results suggest that the effect of warming on periphyton abundance and composition in the different seasons varied with nutrient state and host plant type in these mesocosms, and similar results may likely be found under field conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 85 publications
(100 reference statements)
7
25
0
Order By: Relevance
“…On the other hand, the rapid development of agriculture and industrialization has led to massive inputs of nutrients, especially nitrogen (N) and phosphorus (P), in aquatic environments (Tilman et al, 2001). It has been suggested that the alteration of temperature and nutrient availability will change the ecosystem structure and thereafter threaten the ecological functioning of shallow lakes (Liboriussen et al, 2005;Özkan et al, 2010;Kosten et al, 2012;Hao et al, 2020). Submerged macrophytes are an important component in aquatic ecosystems and usually play a vital role in the ecological functioning of shallow lakes (Jeppesen et al, 2012;Hao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the rapid development of agriculture and industrialization has led to massive inputs of nutrients, especially nitrogen (N) and phosphorus (P), in aquatic environments (Tilman et al, 2001). It has been suggested that the alteration of temperature and nutrient availability will change the ecosystem structure and thereafter threaten the ecological functioning of shallow lakes (Liboriussen et al, 2005;Özkan et al, 2010;Kosten et al, 2012;Hao et al, 2020). Submerged macrophytes are an important component in aquatic ecosystems and usually play a vital role in the ecological functioning of shallow lakes (Jeppesen et al, 2012;Hao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hao et al (2018) and Jones et al (2002) suggested that temperature and nutrients might regulate the growth of submerged macrophytes through the indirect pathway by which rising temperature and nutrient enrichment could induce environmental stress and then cause a decline in the biomass of submerged macrophytes. Furthermore, rising temperature and nutrient enrichment could change abiotic variables, such as dissolved oxygen (DO) and pH, and, thus, influence submerged macrophytes, because DO is necessary for respiration, and pH can determine the availability of inorganic carbon (C) for submerged macrophytes (Jones et al, 2002;Zhang et al, 2015;Dülger et al, 2017;Hao et al, 2020). On the other hand, temperature and nutrients could affect submerged macrophytes through effects on biotic variables, such as the biomass of phytoplankton, periphyton, and zooplankton, since stress from the same trophic level and higher trophic levels may threaten the growth of submerged macrophytes (Jones et al, 2002;Ventura et al, 2008;Hao et al, 2018;Matsuzaki et al, 2018;Yuan and Pollard, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations